(untitled) (Eurasian Journal of History, Geography and Economics, 2023)
The article is devoted to the use of non-standard test tasks in geography classes. In particular, non-standard test tasks developed to determine the extent to which students have mastered this topic in teaching the topic “Lower Amudarya Economic Region” are mentioned